Efficient immunoaffinity chromatography of lymphocytes directly from whole blood. Issue 1 (December 2018) - Mohr, Fabian; Przibilla, Sabine; Leonhardt, Franziska; Stemberger, Christian; Dreher, Stefan; Müller, Thomas R.; Fräßle, Simon P.; Schmidt, Georg P.; Kiene, Marie-Luise; Stadler, Herbert; Busch, Dirk
Abstract We show that defined lymphocytes can be rapidly purified by immunoaffinity chromatography starting directly from whole blood. The method relies on low-affinity Fab-fragments attached to a column-matrix combined with the reversible Strep-tag technology. Compared to established cell enrichment protocols, the Strep-tag affinity chromatography of cells is independent of erythrocyte lysis or centrifugation steps, allowing for simple cell-enrichment with good yields, high purities, and excellent functionality of purified cells.